NILAI KEISLAMAN DAN KEARIFAN LOKAL DALAM PENGEMBANGAN PARIWISATA HALAL PASCA COVID 19 DI KOTA MALANG - Budiyono Santoso; Muhammad Djakfar (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
Cultural and religious values ​​have great potential in the development of halal tourism. Religious values ​​and local wisdom can play a role both in destination development and in tourist services. The city of Malang as one of the pilots of the halal tourism city project, can take advantage of Islamic values ​​and local wisdom that exists in the community to develop halal tourism. This article seeks to explore Islamic values ​​and local wisdom of the people of Malang City and their implementation in the development of halal tourism. This study proposes prophetic traits (shiddiq, amanah, tabligh, fathonah) as Islamic values ​​to be used in the development of halal tourism in Malang City. Meanwhile, diversity, progressiveness and egalitarianism are values ​​of local wisdom that support the development of Halal tourism in Malang City. The prophetic nature in the development of halal tourism in Malang is implemented, one of which is the commitment to meet the standard of the halal assurance system, Clean, Health, Safety, and Environmental Sustainability (CHSE) certification, attention to environmental sustainability, community empowerment and the development of promotional innovations with information technology and social media. While the "arek" culture in Malang City with the characteristics of diversity, open to change, adaptable, egalitarian and progressive is implemented in the development of thematic villages and the active role of the community in the development of tourist destinations in Malang City.